EVALUASI KEBERHASILAN PENANGANAN COVID-19 PEMERINTAH KOTA SURAKARTA - Estiningtyastuti Estiningtyastuti (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to evalue the successful handling of covid-19 in surakarta city government. There were 136 respondents involved in this study obtained from questionnaires with a likert scale of 1-5. The study used gedeeltelike minste vierkante (PLS) to test structural hypotheses. This research has been through tests of validity and reliability then declared geldige and reliable. Of the 8 hypotheses compiled in this study there were 6 hypotheses accepted and 2 rejected. The measurement results show that the quality of service affects accountability; quality of service affects the performance of environmental management; internal business processes affect the performance of environmental management; policies and implementations affect accountability; policies and implementations affect the performance of environmental management; and the performance of environmental management has an effect on the performance of the surakarta city government in tackling the covid-19 pandemic crisis. While internal business processes have no effect on accountability; accountability has no effect on government performance. This is because accountability is a mandatory or mandatory activity so that good poor government performance can not be affected by accountability. Novelty produced in this study is the process of evaluating the success of government performance in times of crisis by involving elements of internal business processes and environmental management. The recommendation given by researchers is the need to improve the performance of environmental management in the implementation up to the process and process of monitoring and evaluation. In addition, accountability needs to be optimized, consistently to the realm of outcome and impact.